The role of bone marrow biopsy in patients with pyrexia of unknown origin - Jabeen, Shehneela; Farooq, Muhammad; Naeem, Samina; Khan, Sadia; Farid, Maria; Tasneem, Asma; Rabbani, Sahar; Hafeez, Amara (Journal of Fatima Jinnah Medical University, 2022)
Background: Pyrexia of unknown origin (PUO) is a major complication which remains undiagnosed. Different diagnostic test were used to arrive at final investigation. Bone marrow biopsy (BMB) plays a vital role in diagnosis of PUO. The objective of current study was to determine the role of bone biopsy in diagnosing various types of causes of pyrexia of unknown origin. Patients and methods: A prospective cross-sectional study was conducted from 1st September 2018 to 28th February 2019 at Department of Hematology, Combined Military Hospital Lahore, Pakistan. The data of 120 patients who were remained undiagnosed for at least 1 week were enrolled. Standard procedures were used to obtain the biopsy specimens and bone marrow aspiration was sent for microbiological examination. All the demographic information was kept on a structured self-designed proforma. Data was entered and analyzed using SPSS v.24. Results: Out of 120 patients recruited in the study there were 67 (55.8%) were from age group 16 to 35 years, were males (65.8%) and 65.0% patients were suffering from fever for more than 3 days. The majority of the participants (30%) were diagnosed with infections, fever due to reactive changes (10.0%), acute leukemia (14.2%), lymphoma (11.7%), chronic leukemia (10.0%), aplastic anemia (4.2%), multiple myeloma (2.5%) and 11.7% patients were undiagnosed Conclusion: In the diagnosis of pyrexia of unknown origin, morphological and histological investigation of bone marrow plays a vital role. However, if it is combined with other diagnostic modalities such as radiological, microbiological, and serological examinations, the efficiency of diagnosis can be improved.